The influence of gender roles and traditional healing on cervical screening adherence amongst women in a Cape Town peri-urban settlement - Despina Learmonth; Anica Jansen van Vuuren; Chantelle De Abreu (South African Family Practice)
Background: Cervical cancer is the third most common gynaecologic malignancy worldwide and is the second most common cancer among South African women. Although entirely preventable, cervical cancer is responsible for the death of approximately 3 027, 53% of those diagnosed, South Africa women annually. A variety of factors influence women’s cervical screening adherence.